Discussion of Accounting for Research and Development Costs: The Impact on Research and Development Expenditures - Ball, Ray (Journal of Accounting Research, 1980)
Ray Ball, Discussion of Accounting for Research and Development Costs: The Impact on Research and Development Expenditures, Journal of Accounting Research, Vol. 18, Studies on Economic Consequences of Financial and Managerial Accounting: Effects on Corporate Incentives and Decisions (1980), pp. 27-37